Analisis Strategi Bisnis Pada Perusahaan Layanan Internet Fixed Broadband Menggunakan Matriks IFE-EFE-IE - Timothy Jordan Christianto; Theofilo Gilroy Jacobus; Ester Yemima Eliana; Imanuel Adhitya Wulanata Chrismastianto (FKIP Universitas Lampung, 2021)
The Covid-19 pandemic has had a significant impact on all community activities, one of which is the change in communication patterns that have been using face-to-face activities now switch to using technology devices to communicate remotely, so this has encouraged fixed broadband internet service providers to compete to provide excellent quality service to their customers. . The purpose of this study is to provide appropriate recommendations regarding business strategies that fixed broadband internet service companies can implement through analysis of the IFE-EFE-IE matrix. The research design used is quantitative through respondent data collection (survey) of 55 people who use fixed broadband internet services calculated using the Expert Choice application version 11. The data obtained were analyzed using the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation Matrix ( EFE), and the Internal-External (IE) matrix. The study results suggest that the business strategies for fixed broadband internet service companies that can be implemented are market penetration strategies and product development strategies. Keywords: Strategy, fixed broadband, IFE, EFE, IE